2023
DOI: 10.21580/pjpp.v8i1.14733
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of college students: The effects of state anxiety and academic stress with self-control as a mediator

Nadya Ariyani Hasanah Nuriyyatiningrum,
Khairani Zikrinawati,
Puji Lestari
et al.

Abstract: College education is expected to equip students with various types of knowledge. In reality, however, the learning process is not always easy. Problems can occur and affect students' quality of life. This study aims to examine the effect of state anxiety and academic stress on the quality of life through the mediation of student self-control. A quantitative method was used involving a sample of 400 students from 24 provinces in Indonesia. The measuring instruments employed were the World Health Organization Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…Previous research has consistently demonstrated that girls are more worried than boys [51]. A low QOL and increased disease activity have been associated with anxiety [52,53]. Anxiety disorders have been linked to a lower QOL in a variety of categories, including physical, psychological, social, and environmental aspects [54].…”
Section: Anxiety and The Qolmentioning
confidence: 99%
“…Previous research has consistently demonstrated that girls are more worried than boys [51]. A low QOL and increased disease activity have been associated with anxiety [52,53]. Anxiety disorders have been linked to a lower QOL in a variety of categories, including physical, psychological, social, and environmental aspects [54].…”
Section: Anxiety and The Qolmentioning
confidence: 99%
“…Emotional disorder with regard to self-esteem and social acceptance may interfere with daily activities and contribute to social interaction problems with peers and family members (Parkinson et al, 2017). Negative emotions are often formed in certain circumstances which have a negative impact on how these emotions manifest (Bombari et al, 2017;Nuriyyatiningrum et al, 2023). It is crucial to understand that emotions expressed in negative thoughts can lead to suicidal ideation, drug use, prostitution and depression (Kaufmann et al, 2019;Wu et al, 2018;You et al, 2018).…”
Section: Introductionmentioning
confidence: 99%